Dynamics Of Integration Of Cireundeu State Law And Customary Law In Resolution Of Social Conflicts Max Weber'S Social Action Perspective - Damayanti, Sri; Marwan, Fatih; Ardiana, Hari; Muhammad , Akmal (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This research examines the dynamics of integration between state law and customary law in resolving social conflicts within the Cireundeu Indigenous Community, using Max Weber’s social action perspective. Cireundeu, located in Cimahi, West Java, represents a unique example of how traditional customs persist amidst modernization. The study reveals that social conflicts, such as inheritance disputes and inter-community marriages, often arise due to differences between customary values and state law. Cireundeu society resolves these conflicts through deliberative mechanisms rooted in customary law, emphasizing dialogue, solidarity, and social harmony.The findings highlight the complementary yet sometimes conflicting roles of state and customary law. While state law provides universal legal frameworks, customary law in Cireundeu prioritizes principles of equality, as seen in its gender-neutral inheritance practices. The resolution of disputes through customary deliberations reflects Weber’s concept of value-rational social action, wherein decisions are guided by adherence to communal values rather than pragmatic considerations.Despite the effectiveness of customary approaches in fostering social cohesion, the research identifies challenges in integrating customary law with state law, particularly due to limited formal recognition of indigenous rights. This gap underscores the need for inclusive policies, such as the Indigenous Peoples Law Bill, to bridge the two legal systems. The study concludes that customary traditions not only contribute to social harmony but also serve as valuable assets in Indonesia’s plural legal system. Further research is recommended to explore the impact of external factors, such as globalization, on the evolution of customary law in Cireundeu and other indigenous communities. Keywords: Cireundeu, Customary law, legal pluralism, social action, social conflict, state law.